Outcomes Following Hypofractionated Stereotactic Radiotherapy in the Management of Brain Metastases. (August 2016) - Ahmed, Kamran A.; Sarangkasiri, Siriporn; Chinnaiyan, Prakash; Sahebjam, Solmaz; Yu, Hsiang-Hsuan Michael; Etame, Arnold B.; Rao, Nikhil G.
Abstract : Objective: To evaluate the outcomes of patients treated with hypofractionated stereotactic radiotherapy (HSRT) for radiosensitive and radioresistant brain metastases. Methods: Between August 2006 and July 2013, a total of 56 lesions in 44 patients with brain metastases were treated with HSRT. Twenty-three (41.1%) lesions were radioresistant. Patients were treated to a total dose of 24 to 30 Gy in 3 to 5 fractions. Median planning target volume was 6.18 cm 3 . The primary endpoint for this study was local control with secondary endpoints of overall survival, distant failure, performance status, and treatment toxicity. Results: The median follow-up for all patients was 5 months (range, 0.4 to 58.3 mo). Six- and 12-month Kaplan-Meier estimates of local control for all lesions were 85.6% and 79.4%, respectively. Radioresistant tumors had a 6- and 12-month local control rate of 87.0%, whereas radiosensitive tumors had a 6- and 12-month local control rate of 82.5% and 72.2%, respectively ( P =0.41). Six- and 12-month distant brain control rates were 56.8% and 46.9%, respectively. Overall survival was significantly associated with recursive partitioning analysis classes I, II, and III ( P =0.0003) and graded prognostic assessment classes 2 to 3 and 1 to 1.5 ( P =0.041). Conclusions: HSRT is a safe and feasible alternative to single-session stereotactic radiosurgery for brain metastases. No difference was observed in local control rates between radioresistant and radiosensitive tumors.